A Linear Structural Equation Model for Covert Verb Generation Based on Independent Component Analysis of fMRI Data from Children and Adolescents - Karunanayaka, Prasanna; Schmithorst, Vincent J.; Vannest, Jennifer; Szaflarski, Jerzy P.; Plante, Elena; Holland, Scott K. (Frontiers in Systems Neuroscience, 2011)
Human language is a complex and protean cognitive ability. Young children, following well defined developmental patterns learn language rapidly and effortlessly producing full sentences by the age of 3 years. However, the language circuitry continues to undergo significant neuroplastic changes extending well into teenage years. Evidence suggests that the developing brain adheres to two rudimentary principles of functional organization: functional integration and functional specialization. At a neurobiological level, this distinction can be identified with progressive specialization or focalization reflecting consolidation and synaptic reinforcement of a network (Lenneberg 1967; Muller, Rothermel et al. 1998; Berl, Vaidya et al. 2006). In this paper, we used group Independent Component Analysis (ICA) and linear structural equation modeling (LSEM) (McIntosh and Gonzalez-Lima 1994; Karunanayaka, Holland et al. 2007) to tease out the developmental trajectories of the language circuitry based on fMRI data from 336 children ages 5-18 years performing a blocked, covert-verb generation task. The results are analyzed and presented in the framework of theoretical models for neurocognitive brain development. This study highlights the advantages of combining both modular and connectionist approaches to cognitive functions; from a methodological perspective, it demonstrates the feasibility of combining data driven and hypothesis driven techniques to investigate the developmental shifts in the semantic network.